DETERMINATION OF TRACE METALS IN PLANT LEAVES AS BIOMONITOR OF POLLUTION EXTENT BY A SENSITIVE STAT-AAS METHOD - Kaya, Gokce; Yaman, Mehmet (Taylor & Francis Inc, 2012)
The aim of this study is to assess the potential of bioindicator/biomonitor plants to determine pollution extent of toxic metals. Lead, cadmium, and copper concentrations in the plants including Platanus sp., Olea europaea L., Vitis vinifera L., and Armeniaca sp. taken from the industrial area of the city of Gaziantep, Turkey, and control location were determined by using STAT-atomic absorption spectrometry. Lead concentration in leaves of Platanus sp. taken from 50m around the battery plant was found to be higher than 3,000 mg kg(-1). The observed Pb concentration in this plant was 40 times higher than that in Armeniaca sp. grown in the same location. The limits of detection for plants were found to be 0.050 mg kg(-1) for Pb and Cu and 0.005 mg kg(-1) for Cd. It was concluded that the Platanus sp. plant can be considered as both biomonitor and hyperaccumulator.
Keywords: biomonitor plants; lead battery; metals; pollution; STAT-AAS